Self-reported tooth and implant prognosis evaluation based on radiographic bone loss: a cross sectional study - Clark-Perry Danielle; Baybrook Jaimie; Catunda Raisa; Levin Liran ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2020)
Introduction: Tooth prognosis evaluation involves continual assessments to guide patient-centered treatment plans. This means that the tooth prognosis may dictate whether a tooth is restored, extracted, or maintained.